Analysis Of Consumer Perceptions And Preferences In Selecting A University For Higher Education - Salsabila, Farha; Mukti Ali, Mochammad (Dinasti International Journal of Management Science, 2024)
This research aims to explore consumers perceptions and preferences in choosing a university as a place to pursue higher education. This research is a qualitative study using interactive analysis primary and secondary data with data collection techniques including in-depth interviews with seven student informants of University of Indonesia Membangun known as INABA University, and analysis of related documents. The results show that there are internal and external factors of perceptions such as university reputation, quality of study programs, location, tuition fees, and flexibilities of the course in the decision to choose a university. And also internal factors such as motivation, interest, or psychological characteristics, from which students eventually choose Inaba as their university preference. This research contributes to an in-depth understanding of the factors that influence consumers decision to choose a university, as well as practical implications for higher education institutions to enhance their appeal. By understanding consumer preferences and perceptions, universities can develop marketing strategies improvements to meet prospective students expectations and build a positive image in the higher education market.